Sweet Potatoes Consumption Against Hemoglobin Levels Of Pregnant Women In The Third Trimester - Susilawati Susilawati; Dina Dwi Nuryani; Siti Khomsatun; Saffanah Saffanah (JKM (Jurnal Kebidanan Malahayati), 2021)
Background: Anemia is one of the most indirect causes of bleeding in maternity women. The effects of anemia at the time of delivery include his dystocia, the strength of pushing, the first stage, which lasts a long time, the third stage, which is followed by the retained placenta and postpartum hemorrhage due to uterine atony, and the fourth stage, which occurs secondary postpartum hemorrhage and uterine atony. One way to increase hemoglobin levels in pregnant women is to increase nutritious food. Here, sweet potatoes have high nutritional value, rich in vitamins and minerals.Objective: To know the effect of sweet potato consumption on hemoglobin levels of pregnant women in the third trimester (TM III) at Puskesmas Branti, South Lampung Regency, in 2020.Research methods: This quantitative used a quasi-experimental research design and two group pretest-posttest research methods. The population in this study was all pregnant women in TM III who performed antenatal care (ANC) at Puskesmas Branti, South Lampung Regency, in March, as many as 138 respondents, with a total sample of 20 pregnant women, of which 10 were the intervention group and 10 were the control group. The research sample was taken using the purposive sampling technique.Research results: Based on data analysis, at Puskesmas Branti, South Lampung Regency, in 2020, the mean Hb level of respondents before the intervention consuming sweet potatoes was 11.230 (10.6-11.7), and after the intervention consuming sweet potatoes was 12.530 (11.4-13.2). Meanwhile, the mean Hb level of intervention respondents before consuming Fe tablets was 11.060 (10.1-11.8), and after consuming Fe tablets, it was 11.870 (11.2-12.5). Conclusion: Based on bivariate analysis using the paired sample t-test, the p-value was <0.05, which was 0.000, meaning that there was an effect of sweet potato consumption on the hemoglobin level of pregnant women in the third trimester at Puskesmas Branti, South Lampung Regency in 2020.Suggestion: From the results of this study, it is hoped to take advantage of the presence of sweet potatoes in the home environment. Keywords: Pregnant Women, Hemoglobin Level, Sweet Potato ABSTRAK KONSUMSI UBI JALAR TERHADAP KADAR HEMOGLOBIN IBU HAMIL TRIMESTER III Latar Belakang: Anemia merupakan salah satu penyebab tidak langsung terjadinya perdarahan terbanyak pada ibu bersalin. Pengaruh anemia pada saat persalinan yaitu gangguan his, kekuatan mengejan, kala pertama dapat berlangsung lama, kala uri dapat diikuti retensio plasenta dan perdarahan post-partum karena atonia uteri, kala empat dapat terjadi perdarahan post-partum sekunder dan atonia uteri. Salah satu cara untuk meningkatkan kadar hemoglobin pada ibu hamil yaitu dengan cara meningkatkan makanan bergizi. Ubi jalar memiliki nilai gizi yang tinggi, kaya vitamin, dan mineral.Tujuan penelitian: Diketahui Pengaruh konsumsi ubi jalar terhadap kadar hemoglobin ibu hamil trimester III di Puskesmas Branti Kabupaten Lampung Selatan Tahun 2020.Metode Penelitian: Jenis penelitian kuantitatif dengan rancangan penelitian quasi eksperimen dan metode penelitian Two group pretest posttest. Populasi dalam penelitian ini adalah seluruh ibu hamil TM III yang melakukan Antenatal Care (ANC) di Puskesmas Branti Kabupaten Lampung Selatan pada bulan Maret adalah sebanyak 138 responden dengan jumlah sampel sebanyak 20 ibu hamil, dimana 10 sebagai kelompok intervensi dan 10 sebagai kelompok kontrol. Pengambilan sample penelitian menggunakan teknik purposive sampling.Hasil Penelitian: Berdasarkan analisis data, diketahui bahwa Di Puskesmas Branti Kabupaten Lampung Selatan Tahun 2020, rata-rata kadar Hb responden intervensi sebelum mengkonsumsi ubi jalar 11,230 (10,6 – 11,7) dan sesudah mengkonsumsi ubi jalar 12,530 (11,4 – 13,2), sedangkan rata-rata kadar Hb responden intervensi sebelum mengkonsumsi tablet Fe 11,060 (10,1 – 11,8) dan sesudah mengkonsumsi tablet Fe 11,870 (11,2 – 12,5).Kesimpulan: Berdasarkan analisis bivariat dengan menggunakan uji Paired Sample T-Test, diketahui nilai p-value < 0,05 yaitu 0,000 yang artinya ada pengaruh konsumsi ubi jalar terhadap kadar hemoglobin ibu hamil trimester III di Puskesmas Branti Kabupaten Lampung Selatan Tahun 2020.Saran: Hasil penelitian ini diharapkan agar dapat memanfaatkan adanya ubi jelar disekitar lingkungan rumah. Kata Kunci: Ibu Hamil, Kadar Haemoglobin, Ubi Jalar